2003
DOI: 10.1021/bi034995k
|View full text |Cite
|
Sign up to set email alerts
|

Lipid−Protein Interactions Studied by Introduction of a Tryptophan Residue:  The Mechanosensitive Channel MscL

Abstract: Trp fluorescence spectroscopy is a powerful tool to study the structures of membrane proteins and their interactions with the surrounding lipid bilayer. Many membrane proteins contain more than one Trp residue, making analysis of the fluorescence data more complex. The mechanosensitive channels MscL's of Mycobacterium tuberculosis (TbMscL) and Escherichia coli (EcMscL) contain no Trp residues. We have therefore introduced single Trp residues into the transmembrane regions of TbMscL and EcMscL to give the Trp-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 45 publications
9
127
0
Order By: Relevance
“…Recent work has reported changes in lipid composition in cells grown at high osmolarity (39). Because MS channels should be particularly sensitive to their lipid environment (40)(41)(42), the inability to observe the activity of wild-type YbdG in patch clamp may reflect differences between lipid compositions of the cells used in the two assays. Physiological assays are conducted on cells grown at high osmolarity whereas cells for patch clamp are grown at low osmolarity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has reported changes in lipid composition in cells grown at high osmolarity (39). Because MS channels should be particularly sensitive to their lipid environment (40)(41)(42), the inability to observe the activity of wild-type YbdG in patch clamp may reflect differences between lipid compositions of the cells used in the two assays. Physiological assays are conducted on cells grown at high osmolarity whereas cells for patch clamp are grown at low osmolarity.…”
Section: Discussionmentioning
confidence: 99%
“…A simulation of MscL in bilayers of PC suggested that the loss of hydrogen bonding observed in bilayers of PC is compensated for by a conformational change in the C-terminal region of MscL, bringing the C-terminal region closer to the membrane and leading to stronger interactions with the membrane (42). This compensating conformation change could be the reason why the binding constants of MscL for DOPE and DOPC are very similar (24,27) as well as the reason for the different effects of DOPE and DOPC on function reported here.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that binding of lipid to MscL can be studied by fluorescence quenching methods, observing the effects of bromine-containing phospholipids on the intensity of Trp fluorescence of a Trp residue introduced into MscL (24,27,30,35). Bromine-containing phospholipids are made by addition of bromine across the double bonds of phospholipids containing two oleoyl chains.…”
Section: Are There Specific Binding Sites For Anionic Lipid On E Colmentioning
confidence: 99%
“…Experimental work showed that the functional properties of the mechanosensitive channel of large conductance (MscL) are affected by variations in lipid composition [192][193][194]. MD has also been used to investigate the effects of such lipid compositions on the protein at a molecular level.…”
Section: Protein/lipid Interactionsmentioning
confidence: 99%